Artificial Intelligence (AiI, Pemasaran Digital Dan Popularitas Terhadap Niat Beli Konser Virtual Pada Girlband Korea Aespa - Fadila Putri Aisya Ramadhini; Alshaf Pebrianggara; Mochamad Rizal Yulianto; Rizky Eka Febriansah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate the influence of artificial intelligence, digital marketing, and popularity on the purchase intention of virtual concerts Korean girlband aespa held on the Beyond Live application. The research design employed in this study is quantitative, and data were collected through the distribution of questionnaires, which were measured using a Likert scale and analyzed using SPSS Version 25. The sample size for this study comprised 100 respondents, selected using purposive random sampling. The results indicate that artificial intelligence has a positive and significant impact on purchase intention, with a t-value of 2.061 and a significance value of 0.011. Similarly, digital marketing has a positive and significant influence on purchase intention, with a t-value of 2.465 and a significance value of 0.015. Furthermore, popularity significantly and positively affects purchase intention, with a t-value of 8.747 and a significance value of 0.000.